The Role of Organizational Citizenship Behavior in Implementing Anti-Fraud Strategies at Bank Sulselbar - Ahmad Fadlan; Didik Ibrahim (Generasi Sains Indonesia, 2025)
The implementation of effective anti-fraud strategies relies not only on clear policies and procedures but also on the involvement of all members across the organization. In this case, organizational citizenship behavior plays a very important role. This study aims to analyze organizational citizenship behavior in the implementation of anti-fraud strategies at Bank Sulselbar in South Sulawesi and West Sulawesi Provinces. This study uses a descriptive quantitative research approach with data collection methods, namely questionnaires and review documents. Samples in this research are Bank Sulselbar employees. Data sources consist of primary and secondary data. While the technique of data analysis uses inferential statistics. The results of the study show that organizational citizenship behavior in implementing anti-fraud strategies at Bank Sulselbar in South Sulawesi and West Sulawesi Provinces is 20,730 or 88% of the maximum percentage. If seen from the value range table it can be concluded that organizational citizenship behavior in implementing anti-fraud strategies at Bank Sulselbar in South Sulawesi and West Sulawesi Provinces is relatively very high.